Utilization of Hyperdocs in Online Learning Models on Student Learning Outcomes - Hasmawati Hasmawati; Daud K. Walanda; Afadil Afadil; Kasmudin Mustapa; Detris Poba (Universitas Tadulako, 2022)
This study aims to improve student learning outcomes through online learning models by utilizing hyperdocs on buffer solution material in class XI MAN 1 Palu City. This type of research uses a quasi-experiment with a pretest and posttest Group Design. Quantitative descriptive research with mixed methods and sampling by purposive sampling. The sample in this study were students of class XI MIPA 1 as the experimental class and XI MIPA 3 as the control class. The instrument used in this study was a learning achievement test totaling 16 multiple-choice question numbers. The research results were obtained from both classes, namely for the experimental class of 81.14 and the control class of 77.05. Learning outcomes were analyzed by testing the effect size for the experimental class, namely 1.2 (Very Large) and 1.0 (Large) for the control class. Based on the results of the study it can be concluded that the online learning model by utilizing hyperdocs in class XI MAN 1 Palu City students can improve student learning outcomes.